Drug testing and corporate responsibility: The “ought implies can” argument - Moore, Jennifer (Journal of business ethics, 1989)
Most of the debate about drug testing in the workplace has focused on the right to privacy. Proponents of testing have had to tackle difficult questions concerning the nature, extent, and weight of the privacy rights of employees. This paper examines a different kind of argument — the claim that because corporations are “responsible” for harms committed by employees while under the influence of drugs, they are entitled to test for drug use. This argument has considerable intuitive appeal, because it seems, at least at first glance, to bypass the issue of privacy rights altogether. The argument turns, not on rights, but on the nature and conditions of responsibility. We may therefore call it an “ought implies can” argument., In spite of its initial appeal, however, the argument does not succeed in circumventing the claims of privacy rights. Even responsibility for the actions of others does not entitle us to do anything at all to control their behavior; we must look to rights, among other things, to determine what sorts of controls are morally permissible. In addition, the argument rests on unjustified assumptions about the connection between drug testing and the prevention of drug-related harm.